PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA KELAS VIII SMP NEGERI 32 SOLOK SELATAN - Yanti, Sovfia Helmida (Jurnal Edukasi dan Penelitian Matematika, 2024)
Mathematical literacy encompasses the ability to formulate, apply, and interpret mathematics across various contexts. It is essential for students to cultivate these skills to tackle real-world problems effectively and improve their competencies. Despite this, the current level of mathematical literacy among eighth-grade students at SMP Negeri 32 Solok Selatan remains suboptimal. To address this issue, the discovery learning model, which emphasizes exploration, is being considered. The aim is to assess whether students who engage in discovery learning exhibit better mathematical literacy skills compared to those who receive direct instruction. This study employs a quasi-experimental design with a static group comparison. It involves an experimental group (Class VIII.1) and a control group (Class VIII.2). A mathematical literacy test serves as the research instrument, with data analyzed using a t-test.Keywords– Discovery Learning Model, Mathematical Literacy Ability, Direct Learning